Diffraction of Sound Waves from Cavity with Inner Lining and Wall Thickness - TİRYAKİOĞLU, BURHAN (My University, 2022)
By applying the Wiener–Hopf and mode matching technique, the diffraction of sound waves by a circular cylindrical cavity with an inner lining is analyzed. In this study, it is assumed that the pipe walls are of a certain thickness, which makes the problem more interesting. Problems in which it is usually assumed that the walls are infinitely thin are not realistic for modeling, since in practice every wall has a certain thickness. While solving our case, an infinite system of algebraic equations is obtained, and the system is solved numerically by truncating to the certain numbers. Finally, graphs of some parameters, such as cavity thickness and depth, are produced for the diffracted field phenomenon, and the consistency of the results is compared with a study available in the literature. topics: cavity, wall thickness, Wiener–Hopf
Keywords: Fizik; Disiplinlerarası Fizik ve İlgili Bilim ve Teknoloji Alanları; Temel Bilimler; Physics; Interdisciplinary Physics and Related Science and Technology Areas; Natural Sciences; FİZİK, MULTİDİSİPLİNER; Temel Bilimler (SCI); PHYSICS, MULTIDISCIPLINARY; PHYSICS; Natural Sciences (SCI); cavity; wall thickness; Wiener-Hopf; CYLINDRICAL DUCT; ACOUSTIC-IMPEDANCE; RADIATION; SCATTERING; PIPE; FLOW; cavity; wall thickness; Wiener–Hopf